2017
DOI: 10.3389/fnmol.2017.00225
|View full text |Cite
|
Sign up to set email alerts
|

Implications of DNA Methylation in Parkinson’s Disease

Abstract: It has been 200 years since Parkinson’s disease (PD) was first described, yet many aspects of its etiopathogenesis remain unclear. PD is a progressive and complex neurodegenerative disorder caused by genetic and environmental factors including aging, nutrition, pesticides and exposure to heavy metals. DNA methylation may be altered in response to some of these factors; therefore, it is proposed that epigenetic mechanisms, particularly DNA methylation, can have a fundamental role in gene–environment interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 157 publications
1
63
0
Order By: Relevance
“…Besides oxidative stress, the etiopathogenesis of neurodegenerative diseases recently encompassed the involvement of epigenetic machinery [Ammal Kaidery et al, ]. In PD, DNA methylation has attracted particular attention, and different studies have identified the occurrence of aberrant patterns of global DNA methylation in brains from PD patients [Chuang et al, ; Miranda‐Morales et al, ]. Here, we evaluated whether exposure to 50‐Hz (1 mT) MF might affect global DNA methylation of dopaminergic‐like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides oxidative stress, the etiopathogenesis of neurodegenerative diseases recently encompassed the involvement of epigenetic machinery [Ammal Kaidery et al, ]. In PD, DNA methylation has attracted particular attention, and different studies have identified the occurrence of aberrant patterns of global DNA methylation in brains from PD patients [Chuang et al, ; Miranda‐Morales et al, ]. Here, we evaluated whether exposure to 50‐Hz (1 mT) MF might affect global DNA methylation of dopaminergic‐like cells.…”
Section: Discussionmentioning
confidence: 99%
“…In PD patients, alteration of global and promoter‐specific DNA methylation has been reported [Chuang et al, ; Miranda‐Morales et al, ]. In particular, in post mortem brains of PD patients, the α‐synuclein gene promoter was found to be highly hypo‐methylated [Wullner et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…DNAm is a very stable mechanism, capable of providing reliable measurements from a wide range of biological materials, such as tissue, blood (plasma and serum), sputum, urine, etc., even after long‐term storage (Nogueira da Costa & Herceg, ; Lorincz, ). In the context of therapeutics and biomarker discovery, methylation assays are easy to perform and automate and, in several cases, concordant methylation alterations have been found in different tissues of the human body (Nogueira da Costa & Herceg, ; Masliah et al ., ; Lorincz, ; Miranda‐Morales et al ., ). From an operational point of view, technologies to measure DNAm marks and patterns are now “reproducible, cost‐efficient and amenable to high‐throughput processing” (Ladd‐Acosta, , p. 118).…”
Section: Introductionmentioning
confidence: 97%
“…Currently available treatments for rGBM are unable to effectively overcome the high intratumoral cellular and molecular heterogeneity to elicit sustained tumor regression. Disease complexity may be further enhanced by detrimental effects of cytotoxic chemotherapy and ionizing radiation on genetic and epigenetic stability [15,22,26].Since tumor-associated changes in the gDNA methylation status is replicated in gDNA obtained from peripheral blood cells of cancer patients [38][39][40], analysis of gDNA global methylation status using peripheral mononuclear cells from rGBM patients could be potentially used as a non-invasive prognostic biomarker, representing a valuable circulating screening tool that better represents the dynamic nature of such intracranial malignancy [41].…”
Section: Discussionmentioning
confidence: 99%